Delamanid-containing regimens over 24 weeks for the treatment of multidrug-resistant/rifampicin-resistant tuberculosis: preliminary results from a single center in a multicenter, prospective, observational study - Yang, Fuping; Yin, Mingdan; Jiang, Xingmei; Zhao, Xing; An, Xuemei; Liu, Yan; Yuan, Yijia (Frontiers in Medicine, 2025)
BackgroundSingle center preliminary results from a multicenter, prospective, observational study whose aims were to investigate the efficacy and safety of 24-week delamanid-containing regimens in Chinese multidrug-resistant/rifampicin-resistant tuberculosis (MDR/RR-TB) patients.MethodsThe study included adult patients (≤65 years old) with laboratory-confirmed MDR/RR-TB who were assigned to receive 24 weeks of delamanid (100 mg, twice daily) plus an optimized background regimen (OBR), followed by 5 ~ 12 months of continuation treatment with OBR alone according to World Health Organization and Chinese guidelines.ResultsThirty-three patients were enrolled, 26 of whom completed the entire treatment course (intensive + continuation phases), with a treatment success rate of 78.8% (95% CI, 61.1, 91.0). Among the 29 patients who were baseline culture-positive, sputum culture conversion was observed in 25 (86.2%) patients within 24 weeks of delamanid treatment, with a median time to sputum culture conversion of 38 days (interquartile range: 24–77). A total of 18 (54.6%) patients experienced treatment-emergent adverse events (TEAEs), most of them being grade 1 or 2 in severity. Six (18.2%) patients had delamanid-related TEAEs, of whom 5 (15.2%) discontinued the delamanid treatment due to QT interval prolongation (2, 6.1%), gastrointestinal reactions (2, 6.1%) or atrial premature beat (1, 3.0%).ConclusionThe preliminary findings of the present single-center study indicated that the 24-week delamanid-containing regimen demonstrated a promising treatment outcome in Chinese MDR/RR-TB patients. A 24-week follow-up period of safety outcomes was basically consistent with the overall results of the multicenter investigation, and close monitoring of QT interval prolongation should in particular be carried out when delamanid is combined with clofazimine and levofloxacin.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT04421495, identifier NCT04421495